Mark and Syria? An Assessment. (August 2014) - Carter, Warren
One argument advanced for the Syrian, rather than Roman, provenance of Mark's Gospel concerns geographical proximity to the 66-70 war. This article evaluates this largely unexamined argument, concluding that the attempt to sustain Syrian provenance on the basis of geographical proximity to the events narrated in Mark 13 fails to persuade. This argument cannot show unique correspondences between text and context, and the equation of great effects with geographical proximity fails the tests of Philo's narrative concerning Gaius' threat to the temple, contemporary experience, and contemporary attachment theory (Kirkpatrick) that highlight the key role of psychological attachments that are not restricted by geography.